A case of sustainable intensification: Stochastic farm budget optimization considering internal economic benefits of biogas production in organic agriculture. (January 2018) - Blumenstein, Benjamin; Siegmeier, Torsten; Selsam, Franziska; Möller, Detlev
Abstract: Organic agriculture is often criticized for its lower productivity compared to conventional farming, while biogas production on organic farms is confronted with many structural constraints additionally impeding its profitability. However, integrated anaerobic digestion seems to induce multiple benefits for the respective organic farm system, such as reduced environmental impacts, improved nutrient efficiency, and stabilized or increased yields. In order to measure these effects within entire farm systems, systemic evaluation approaches are needed. Consequently, in this study we modelled twelve different livestock-keeping (LS) and stockless (noLS) organic farm prototypes comprising of arable farming, dairy cattle, grassland, and biogas production in a farm system assessment. The aim was to evaluate the impact of integrated anaerobic digestion (+ AD) on agronomic, economic, and risk aspects by applying stochastic optimization. While the absolute amount of readily available nitrogen as well as cash crop yields increase for both LS + AD and noLS + AD farm models, especially noLS farm types benefit from the novel availability of a mobile nitrogen (N) fertilizer (biogas digestate) to meet cash crop N demands. Integrated AD may increase profitability of arable farming and reduce its risk potential by displaying first order stochastic dominance. In addition, this diversification strategy may reduce the overall production risk of organic farms. By providing renewable energy as well as increasing food outputs and economic stability, the integration of AD in organic farms may serve as an example for the often postulated aim of a sustainable or eco-functional intensification of organic agricultural systems to face the challenge of productivity increases. Highlights: Anaerobic digestion (AD) may induce multiple benefits for organic agriculture (OA). Systemic evaluation approach is applied to evaluate entire OA farm systems. Evaluation model integrates agronomic, profitability, and risk assessment. Farm models with integrated AD display increased food productivity and profits. As case of sustainable intensification, AD in OA resolves food or fuel antithesis.